Limnological parameters in area of influence of cachama (Piaractus brachypomus) cages culture (Orinoquia, 2018)
The parameters of oxygen, temperature, pH, alkalinity, hardness, ammonium, orthophosphate, conductivity, totals solids, transparency, depth and organic matter were monitored to characterize the area of influence of cage culture on water and sediment quality in the Soplaviento Ensenada in the Manacacias River. Trophic State Indexes (IET) estimated phosphorus and nitrogen to determine the trophic state. For temperature, pH, hardness, conductivity and totals solids, not significant effect of sampling was found; suggesting that sampling associated with rainfall cycles strongly influences water quality parameters in this type of system. In terms of trophic status the conditions remained mesotrophic, denoting that the system implemented does not yet represent saturation for the medium.
Keywords: eutrophication; Manacacias river; organic matter; sediment